Soundwalking : through time, space, and technologies - Smolicki, Jacek (Routledge, 2023)
"Soundwalking brings together a diverse group of contemporary scholars, artists and activists in one of the first comprehensive studies of soundwalking - the practice of moving through space while carefully listening to what it has to say - to address urgent challenges and concerns of an environmental, ethical, social, and technological nature. Besides gaining insight into the historical development of soundwalking as a scholarly method and artistic genre, the reader will have a chance to learn from emerging voices concerned with this practice, of many different backgrounds and positionalities. Soundwalking demonstrates how attentive listening and walking might help with more careful and responsible navigation through the complex dimensions of our shared environments and entangled histories, often imperceptible on a day-to-day basis. The book encourages scholars, artists and also those unfamiliar with the concept, to engage with it in their respective fields and subjects of interest as an interdisciplinary method of critical inquiry and a creative mode of communication. This book inspires readers to discover anew the potential of walking and listening and will be of interest to students, researchers and practitioners in the areas of studies directly concerned with sound and beyond, including environmental humanities, landscape architecture, media, and cultural studies"--